Mixed Conjunct Verbs And Other Manifestations Of Hindi Englishization - Borowiak, Tomasz (Investigationes Linguisticae, 2007)
This article aims at describing some lexical exponents of English impact observed in the urban, colloquial variety of Hindi. At the lexical level of the language, the process of Hindi Englishization involves borrowing of lexemes representing major lexical categories and the formation of hybrid structures in which the borrowed and native morphemes meet. Accordingly, we will investigate some crucial aspects of English noun, adjective and adverb insertion, and further along discuss the mixed conjuct verbs, mixed postpositons and the affixation of the borrowed items.